Theatre of Intentionality: Theorizing the Place of Dramatic Intentionality in the Theatre Arts - Ojoniyi, O.W. (My University, 2017)
From studies on the workings of the human consciousness, based on psychoanalytical, phenomenological and existential analyses, conclusions have been drawn that consciousness is always consciousness of something. The argument is simply that consciousness is not just a dormant awareness of ideas or phenomena; it is always directed/prompted at taking action(s) or counter action(s). The prompt for actions or counter actions in consciousness is what Sartre identified as the intentionality of consciousness. In actual fact, Sartre argues that consciousness is intentionality. Appropriating this position, therefore, I have continued to argue that every dramatic art is an act of consciousness, meaning that, every dramatic art is based on certain intentionality of the artist, either as a playwright, play director, actor/actress, light/sound technician, make-up, costumer or theatre critic. There is always an intentionality, the consciousness prompt, behind our actions as theatre practitioners. Consequently, this paper lays bare the theoretical framework christened ‘dialectical text consciousness’ for the argument that every dramatic art is essentially an act that is based on certain intentionality of consciousness. And, it is on the strength of the argument of the paper, an argument which actually developed from my PhD thesis, that I have proposed what is called a “Theatre of Intentionality” in the title of the paper.
Seminar
Keywords: human consciousness; psychoanalytical; playwright; Theatre of Intentionality